Severe agitation in severe early-onset Alzheimer’s disease resolves with ECT - Aksay SS (Dove Medical Press, 2014)
Suna Su Aksay, Lucrezia Hausner, Lutz Frölich, Alexander Sartorius Department of Psychiatry and Psychotherapy, Central Institute of Mental Health, Medical Faculty Mannheim, Heidelberg University, Mannheim, Germany Abstract: Dementia-related behavioral disturbances are mostly treated with antipsychotics; however, the observed beneficial effects are modest and the risk of serious adverse effects high. We report the case of a 57-year-old woman with severe early-onset Alzheimer’s disease and severe agitation, whom we treated with electroconvulsive therapy (ECT). A significant clinical improvement was achieved over eight ECT sessions, which were tolerated well without cognitive worsening, and lasted approximately 3 months. Our case demonstrates the safe and effective use of ECT in pharmacotherapy-resistant severe agitation in Alzheimer’s disease. The risk–benefit profile of ECT for dementia-related agitation should be further investigated in clinical trials. Keywords: dementia, electroconvulsive therapy, cognition, emotional distress, disinhibition.